PENGARUH JOB INSECURITY DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN HOTEL - Januartha, A A Gede Agung; Adnyani, I.G.A Dewi (E-Jurnal Manajemen; Vol 8 No 2 (2019)DO - 10.24843/EJMUNUD.2019.v08.i02.p01, 2019)
Turnover intention will affect the performance and sustainability of the company for the future. The purpose of this research is to analyze the influence of job insecurity and job satisfaction toward turnover intention. The research was conducted at Hotel Grand Zuri Kuta, Badung regency, Bali. The number of respondents in use as many as 75 employees by using the census method .  Data analysis method used is multiple linear regression analysis. Data collecting through, questionnaires and interviews. The results showed that job insecurity had positive and significant effect on turnovrer intention, and job satisfaction had negative and significant effect on turnover intention. To lower the turnover intention rate it is important to pay attention to safety and comfort in working. Therefore it is very necessary to minimize the threats of cyclical and psychological to employees because it will impact on performance and also a strong reference to minimize turnover intention. In addition to job security (job insecurity) job satisfaction is also a strong reference in mempenguruh intention turnover intention. Therefore it is very important to pay attention to job satisfaction from employees to high employee satisfaction level, thus will show the positive level of employees, both to the work and environment. Keywords : job insecurity, job satisfaction, intrntion turnover